Archaeomagnetic dating and magnetic characterization of ceramics from the Paquimé, Casas Grandes region, Chihuahua, Mexico. (June 2021) - Alva-Valdivia, L.M.; Rodríguez-Trejo, A.; Cruz-Antillón, R.; Hervé, G.; Perrin, M.; Salgado-Saito, M.M.; Mahgoub, A.N.
Highlights: Archaeointensity of the Casas Grandes ceramics. Archaeological sites: Paquimé, Galeana, Villa Ahumada and Samalayuca. Archaeointensity: 49–59 µT and 41–49 µT Mimbres and Ramos, respectively. Archaeomagnetic dating: 960–1100 and 1300–1600 AD, Mimbres and Ramos, respectively. Abstract: Casas Grandes is a prehistoric culture area located between Chihuahua, northern Mexico, and New Mexico, southwest of United States of America. It had an intense occupation with large buildings during the ceramic period, from 0 to 1450 CE, developing very particular painted potteries. In this study, magnetic properties and archaeointensity experiments were investigated on two special ceramic types called Mimbres and polychrome Ramos. They come from four archaeological sites from Casas Grandes region in northern Chihuahua: Paquimé, Villa Ahumada, Galeana, and Samalayuca. Archaeological timing and typology assign Mimbres and Ramos to an age period between 900 and 1450 CE, but no absolute ages are available. Magnetic properties show that Mimbres and Ramos have different magnetomineralogical properties, suggesting that pottery making materials were different. Mean archaeointensity results were obtained from nine different pottery sherds, five from Mimbres and four from Ramos polychrome, for a total of 35 specimens. Intensity value range from 49 to 59 µT for Mimbres type and from 41 to 49 µT for Ramos type. Archaeomagnetic dating was performed using the SHAWQ2k global model and the Maghoub regional paleosecular variation curve. Archaeomagnetic dating give an absolute age range of 960–1100 CE for Mimbres type, and of 1300–1600 CE for Ramos samples, confirming that both ceramic types were manufactured at different times. These results highlight the potential of archaeomagnetism to precise the chronological framework of Casas Grandes culture.